DIGITAL TECHNOLOGIES IN EDUCATION: ICT IMPLEMENTATION AND LANGUAGE TEACHING EXPERIENCE ARE EFFECTIVE IN TEACHING THE PRONUNCIATION OF THE KARAKALPAK LANGUAGE - Zhorabekov T. K. (Bright Mind Publishing, 2025)
The phonetics of the Karakalpak language - its pronunciation, sound system, accent, and intonation features - play an important role in the educational process. Digital technologies, as modern teaching methods, are of great help in language teaching. This study examines the effectiveness of teaching phonetics through digital tools, such as mobile applications, phonetic analysis programs, and interactive educational platforms. Also, with the help of these technologies, effective ways to facilitate students' language acquisition, correct pronunciation, and eliminate pronunciation errors are analyzed. The article is aimed at developing methodological foundations for the application of digital technologies in teaching the Karakalpak language, practical application of pedagogical approaches and modern didactic tools.
Keywords: Karakalpak language, phonetics, pronunciation, digital technologies, interactive learning, mobile applications, phonetic analysis, teaching methods, motivation, learning effectiveness.